The influence of competence, motivation and level of education on the performance of archive management in the library and archives office of Sungai Penuh City - Askar Yaya; Moh Erfan Sirad; Alpadli Alpadli; Adlizar Adlizar (Enrichment : Journal of Management, 2023)
This study aims to determine the influence of competence, motivation and level of education on the performance of archive management in the Library Office and the Sungai Penuh City Archives. The research strategy used in this study was to use associative research strategies. The population in this study was 33 employees of the Sungai Penuh City Library and Archives Office. The sample used was 33 people using the full sampling technique or saturated sample. The data analysis technique is multiple linear regression and Coefficient of Determination. The results showed that: (1) Competence has a positive and significant effect on employee performance. (2) Motivasi has a positive and significant effect on employee performance. (3) Education Levelhas a positive and significant effect on employee performance. (4) Competence, motivation and level of education together have a positive and significant effect on the performance of employees of the Library Service and the Sungai Penuh City Archives.